The detection of cryptic Plasmodium infection among villagers in Attapeu province, Lao PDR. - Moritoshi Iwagami; Sengdeuane Keomalaphet; Phonepadith Khattignavong; Pheovaly Soundala; Lavy Lorphachan; Emilie Matsumoto-Takahashi; Michel Strobel; Daniel Reinharz; Manisack Phommasansack; Bouasy Hongvanthong; Paul T Brey; Shigeyuki Kano (Public Library of Science (PLoS), 2017)
Although the malaria burden in the Lao PDR has gradually decreased, the elimination of malaria by 2030 presents many challenges. Microscopy and malaria rapid diagnostic tests (RDTs) are used to diagnose malaria in the Lao PDR; however, some studies have reported the prevalence of sub-microscopic Plasmodium infections or asymptomatic Plasmodium carriers in endemic areas. Thus, highly sensitive detection methods are needed to understand the precise malaria situation in these areas.A cross-sectional malaria field survey was conducted in 3 highly endemic malaria districts (Xaysetha, Sanamxay, Phouvong) in Attapeu province, Lao PDR in 2015, to investigate the precise malaria endemicity in the area; 719 volunteers from these villages participated in the survey. Microscopy, RDTs and a real-time nested PCR were used to detect Plasmodium infections and their results were compared. A questionnaire survey of all participants was also conducted to estimate risk factors of Plasmodium infection. Numbers of infections detected by the three methods were microscopy: P. falciparum (n = 1), P. vivax (n = 2); RDTs: P. falciparum (n = 2), P. vivax (n = 3); PCR: Plasmodium (n = 47; P. falciparum [n = 4], P. vivax [n = 41], mixed infection [n = 2]; 6.5%, 47/719). Using PCR as a reference, the sensitivity and specificity of microscopy were 33.3% and 100.0%, respectively, for detecting P. falciparum infection, and 7.0% and 100.0%, for detecting P. vivax infection. Among the 47 participants with parasitemia, only one had a fever (≥37.5°C) and 31 (66.0%) were adult males. Risk factors of Plasmodium infection were males and soldiers, whereas a risk factor of asymptomatic Plasmodium infection was a history of ≥3 malaria episodes.There were many asymptomatic Plasmodium carriers in the study areas of Attapeu province in 2015. Adult males, probably soldiers, were at high risk for malaria infection. P. vivax, the dominant species, accounted for 87.2% of the Plasmodium infections among the participants. To achieve malaria elimination in the Lao PDR, highly sensitive diagnostic tests, including PCR-based diagnostic methods should be used, and plans targeting high-risk populations and elimination of P. vivax should be designed and implemented.